(untitled) (Applied Biological Research, 2019)
Malaria is a mosquito-borne infectious disease of humans caused by eukaryotic protists of genus Plasmodium. Plasmodium falciparum is mainly responsible for severe form of malaria while malaria caused by P. vivax, P. ovale and P. malariae is characteristically milder disease and seldom fatal. The present study was undertaken to characterize the function and structure of a hypothetical protein from Plasmodium vivax sal-1 (Accession No XP-001615924.1) retrieved from NCBI. Different tools and databases were used to predict the function and structure of this hypothetical protein. The results showed the presence of Fasciclin 1 domain in the hypothetical protein. Fasciclin 1domain represents an ancient adhesion domain common in plants and animals. It is an insect neural cell adhesion molecule involved in axonal guidance that is attached to the membrane by a GPI-anchored protein. Results from various in silico studies predicted the role of hypothetical protein in cell adhesion.